External Shocks, Asset Prices, and Credit Dynamics in Morocco: Insights from Disequilibrium Models - Kchikeche, Ahmed; Mafamane, Driss (Ekonomika, 2024)
We investigate external shocks and asset price’s impact on the slowdown of business and household credit in Morocco using disequilibrium models. The results show that banks’ fly to quality, driven by a simultaneous decline in interest margins and borrower creditworthiness, is a key factor behind the slowdown of credit supply. On the demand side, slower growth and saturated housing demand have contributed to reduced borrowing and repayment capacity of borrowers. Furthermore, external shocks are transmitted to credit supply through foreign deposits and households’ credit demand through remittances. Additionally, stocks and residential real estate asset prices are closely tied to credit demand. These findings suggest that addressing bank credit barriers could stimulate economic growth. To do so, policymakers may consider employing unconventional monetary policy tools to effectively manage the transmission channels of external shocks and asset prices to bank credit dynamics.
Keywords: Bank credit; Asset prices; Disequilibrium model; External shocks